Modernism keywords - Cuddy-Keane, Melba; Hammond, Adam.; Peat, Alexandra (Hoboken : Wiley-Blackwell, 2014)
"Modernism: Keywords presents a series of short entries explaining the diverse and often contradictory meanings of words used with frequency and urgency in "written modernism"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2015. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: English language -- Etymology; English language -- Glossaries, vocabularies, etc; Modernism (Literature); Social structure -- Terminology; Culture -- Terminology; Sociolinguistics; Vocabulary; Electronic books